Resin composition, copper-clad plate containing same and printed circuit board

By designing a combination of T-type polyvinyl siloxane resin with a specific vinyl content with maleimide compounds and thermoset polyphenylene ether resin, a new resin composition is formed, which solves the problem of unstable dielectric properties of the existing resin composition in a high humidity environment, and achieves excellent comprehensive performance of low dielectric loss, low thermal expansion and high heat resistance.

CN120230394APending Publication Date: 2025-07-01GUANGDONG SHENGYI SCI TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311838592.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-28
Publication Date
2025-07-01

AI Technical Summary

Technical Problem

The dielectric properties of the existing resin compositions are unstable in high humidity environments, making it difficult to achieve low dielectric loss, low thermal expansion and high heat resistance at the same time.

Method used

A new resin composition is formed by designing a combination of a T-type polyvinyl siloxane resin with a specific vinyl content with a maleimide compound and a thermoset polyphenylene ether resin. The composition improves the crosslinking density through crosslinking reaction and self-polymerization reaction during the compounding process, thereby obtaining the characteristics of low dielectric constant, low dielectric loss and high glass transition temperature.

Benefits of technology

It has achieved good dielectric performance stability in high humidity environments, has low dielectric loss, low hygroscopicity, excellent moisture and heat resistance and dielectric stability, and has excellent overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004638235030000051
    Figure BDA0004638235030000051
  • Figure BDA0004638235030000061
    Figure BDA0004638235030000061
  • Figure BDA0004638235030000063
    Figure BDA0004638235030000063
Patent Text Reader

Abstract

The invention provides a resin composition, and a copper-clad plate and a printed circuit board containing the same. The resin composition comprises the following components in parts by mass: 10-20 parts of T-type polyvinyl siloxane resin, 10-30 parts of a maleimide compound and 30-80 parts of thermosetting polyphenyl ether resin, the content of vinyl in the T-type polyvinyl siloxane resin is greater than or equal to 1.5 mmol / g. Through the design of the T-type polyvinyl siloxane resin and the compounding and mutual cooperation of the T-type polyvinyl siloxane resin, the maleimide compound and the thermosetting polyphenyl ether resin, the resin composition has a low dielectric constant Dk, a low dielectric loss tangent Df, a high glass transition temperature Tg, a low thermal expansion coefficient CTE and low hygroscopicity; the halogen-free flame retardant, excellent heat resistance, humidity and heat resistance and dielectric stability are realized, the phenomenon of dielectric property deterioration in a humid environment is effectively reduced, and the comprehensive performance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of printed circuits, and particularly relates to a resin composition, a copper clad laminate containing the same, and a printed circuit board. Background Art

[0002] With the high performance and multi-functionality of electronic products, their electronic devices are more highly integrated and high-density, and the high-frequency of transmitted signals requires that the substrate material has a low dielectric constant and a low dielectric loss tangent to reduce the damping effect on electrical signals, thereby improving the signal transmission speed and reducing signal transmission loss. Along with the increase in signal frequency and the increase in signal processing volume, not only is it required that the board material has good dielectric properties, but also, in order to avoid reliability problems caused by inconsistent thermal expansion between the printed circuit board (PCB) and the chip, it is also required that the substrate material has the property of low thermal expansion.

[0003] As a low-polarity crosslinkable resin, thermosetting polyphenylene ether resin is widely used in copper clad laminates for high-frequency applications due to its characteristics of low dielectric constant and low dielectric loss factor; in order to improve the heat resistance reliability of polyphenylene ether materials, maleimide compounds with high-temperature resistance characteristics are often introduced into the resin materials to increase its glass transition temperature and reduce thermal expansion at the same time, thereby increasing heat resistance; however, with the complexity of the application environment, products not only have requirements for electrical performance and heat resistance, but also need to maintain good dielectric performance stability in a high-humidity environment to ensure the stable and reliable transmission of signals.

[0004] CN104263306A discloses a polyphenylene ether adhesive, and its resin composition is composed of component raw materials such as a modified low-molecular-weight polyphenylene ether resin, an epoxy resin, a benzoxazine resin, and a bismaleimide resin. The copper clad laminate made of this polyphenylene ether adhesive has good heat resistance, but its dielectric constant and dielectric loss are relatively high, and it cannot reach the level of very low dielectric loss, making it difficult to meet the needs of high-frequency signal large-capacity transmission.

[0005] CN105936745A discloses a resin composition, which contains a DOPO-based phosphorus-containing flame retardant and an active unsaturated bond resin. The active unsaturated bond resin can be one or more of a polyolefin compound, a cyanate resin, a maleimide resin, a vinyl polyphenylene ether resin, triallyl isocyanurate, and triallyl cyanurate, and discloses a prepreg and a copper clad laminate made of vinyl-terminated polyphenylene ether (PPO), styrene-butadiene resin, and maleimide resin; although this resin system has the characteristics of high heat resistance, low dielectric constant, and low dielectric loss, due to the relatively large polarity of the maleimide compound and its large hygroscopicity, it affects the dielectric performance stability of the product during use.

[0006] Therefore, how to provide a resin composition with excellent comprehensive performance, which can maintain good dielectric stability in a high-humidity environment, achieve low dielectric loss characteristics, and can better balance dielectric properties, low thermal expansion and high heat resistance, has become a technical problem to be solved urgently at present. Summary of the Invention

[0007] Aiming at the deficiencies of the prior art, the purpose of the present invention is to provide a resin composition, a copper clad laminate and a printed circuit board containing the same. Through the design of a T-shaped multi-vinyl silicone resin with a specific vinyl content and its compounding and synergy with a maleimide compound and a thermosetting polyphenylene ether resin in a specific proportion, the resin composition realizes high heat resistance, low dielectric loss and low hygroscopicity characteristics, and can effectively reduce the deterioration of dielectric properties in a humid environment, with excellent comprehensive performance.

[0008] To achieve this purpose, the present invention adopts the following technical solutions:

[0009] In the first aspect, the present invention provides a resin composition, which includes the following components in parts by mass:

[0010] T-shaped multi-vinyl silicone resin 10 - 20 parts

[0011] Maleimide compound 10 - 30 parts

[0012] Thermosetting polyphenylene ether resin 30 - 80 parts;

[0013] The content of vinyl in the T-shaped multi-vinyl silicone resin ≥ 1.5 mmol / g.

[0014] The present invention has found through research that due to the large structural polarity and relatively high hygroscopicity of the maleimide compound, it is easy to cause deterioration of the dielectric properties of the resin in a humid and hot environment, affecting its use stability. Therefore, a T-shaped multi-vinyl silicone resin containing a vinyl structure is introduced into the resin composition of the present invention. By utilizing the low hygroscopicity characteristics of silicone, not only the moisture resistance of the resin system containing the maleimide compound can be improved, but also the heat resistance and dielectric properties of the overall system will not be affected, thus expanding the application of the system.

[0015] The resin composition provided by the present invention comprises a combination of a T-shaped polyvinylsiloxane resin, a maleimide compound, and a thermosetting polyphenylene ether resin. The maleimide compound undergoes a cross-linking reaction with the thermosetting polyphenylene ether resin and the T-shaped polyvinylsiloxane resin. In addition, the unsaturated double bonds in the thermosetting polyphenylene ether resin and the T-shaped polyvinylsiloxane resin undergo self-polymerization and mutual reactions among themselves, increasing the rigid imide structure in the system while enhancing the cross-linking density of the resin composition. The cured product thus obtained has the characteristics of low dielectric constant, low dielectric loss tangent, high glass transition temperature (Tg), and low coefficient of thermal expansion (CTE). In particular, it has low hygroscopicity, excellent heat and humidity resistance, and dielectric stability, avoiding the deterioration of dielectric properties in a humid environment.

[0016] The following are preferred technical solutions of the present invention, but do not limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0017] In the resin composition of the present invention, the mass parts of the T-shaped polyvinylsiloxane resin are 10 - 20 parts. For example, it can be 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, or 19 parts, as well as the specific point values between the above point values. Due to space limitations and for the sake of brevity, the present invention does not exhaustively list the specific point values included in the above range.

[0018] The mass parts of the maleimide compound are 10 - 30 parts. For example, it can be 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, or 28 parts, as well as the specific point values between the above point values. Due to space limitations and for the sake of brevity, the present invention does not exhaustively list the specific point values included in the above range.

[0019] The mass parts of the thermosetting polyphenylene ether resin are 30 - 80 parts. For example, it can be 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, or 75 parts, as well as the specific point values between the above point values. Due to space limitations and for the sake of brevity, the present invention does not exhaustively list the specific point values included in the above range.

[0020] Preferably, the T-shaped polyvinylsiloxane resin, the maleimide compound, and the thermosetting polyphenylene ether resin have the above-mentioned mass parts, and the total mass of the three is 100 parts.

[0021] The content of vinyl groups in the T-shaped polyvinyl siloxane resin is ≥ 1.5 mmol / g. For example, it can be 1.8 mmol / g, 2 mmol / g, 2.5 mmol / g, 3 mmol / g, 3.5 mmol / g, 4 mmol / g, 4.5 mmol / g, or 5 mmol / g, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention does not exhaustively list the specific point values included in the range. Further preferably, it is 1.5 - 5 mmol / g. If the vinyl content is too low, the glass transition temperature of the system will decrease and the CTE will increase.

[0022] Preferably, the T-shaped polyvinyl siloxane resin contains at least one RSiO 3 / 2 group and at least one CH2=CH(CH3)2SiO 1 / 2 group; wherein, the R is a phenyl group.

[0023] Preferably, the T-shaped polyvinyl siloxane resin contains (RSiO 3 / 2 ) a (CH2=CH(CH3)2SiO 1 / 2 ) b ((CH3)3SiO 1 / 2 ) c structure; wherein, a, b, and c each independently selected from integers of 1 - 30. For example, it can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 12, 15, 18, 20, 22, 25, 28, or 30, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention does not exhaustively list the specific point values included in the range. Wherein, the R is a phenyl group.

[0024] Preferably, the T-shaped polyvinyl siloxane resin includes a vinyl-containing poly(silsesquioxane) resin.

[0025] Preferably, the T-shaped polyvinyl siloxane resin has a structure shown in Formula I:

[0026]

[0027] Wherein, R1 and R2 each independently selected from any one of;

[0028] -* represents the connection site of the group.

[0029] When R1 and R2 each independently selected from , it means that this group can appear repeatedly, but will eventually be capped.

[0030] m, n, and p are each independently selected from integers from 1 to 15, and for example, can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15. It should be noted that the order of the units where m, n, and p are located is not limited, and it may be random copolymerization or block copolymerization.

[0031] Preferably, the T-shaped polyvinyl siloxane resin exemplarily includes, but is not limited to, PS-GV08 of Silicon Innovation Technology Co., Ltd., YK-253 and YK-252 of Yingke New Materials Co., Ltd.

[0032] Preferably, the maleimide compound is a maleimide resin containing at least two imide ring structures in its molecular structure.

[0033] Preferably, the maleimide compound has the structure shown in Formula II:

[0034]

[0035] Among them, n1 is selected from integers from 1 to 10, and for example, can be 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10, and more preferably 2 - 10.

[0036] L is selected from *-CH2-*, -* represents the connection site of the group.

[0037] R 11 、R 12 、R 13 are each independently selected from any one of C1 - C5 (such as C1, C2, C3, C4, C5) linear or branched alkyl groups, and phenyl groups.

[0038] m1, m2, and m3 respectively represent the numbers of the substituents R 11 、R 12 、R 13 and are each independently selected from integers from 0 to 3, and for example, can be 0, 1, 2, 3; when m1 ≥ 2, multiple R 11 are the same or different groups; when m2 ≥ 2, multiple R 12 are the same or different groups; when m3 ≥ 2, multiple R 13 are the same or different groups.

[0039] s is selected from integers from 1 to 5, and for example, can be 1, 2, 3, 4, 5.

[0040] Preferably, m1 is 2, that is, there are 2 R 11 connected to the benzene ring, one of the R 11 is a methyl group, and the other R 11is methyl, ethyl or propyl; and / or, m2 is 2, that is, there are 2 Rs attached to the benzene ring 12 , where one R 12 is methyl, and the other R 12 is methyl, ethyl or propyl.

[0041] Preferably, the maleimide compound includes a maleimide compound having a structure shown in Formula IIA and / or a maleimide compound having a structure shown in Formula IIB;

[0042]

[0043] Preferably, the maleimide compound can be a commercially available product, exemplarily including but not limited to: BMI-70, BMI-50P of KI Company; BMI-5100, BMI-2300 of Daiwa Chemical; DFE933, DFE936, DFE950, DFE950A of Dongcai Technology; MIR-3000, MIR-5000 of Nippon Kayaku Co., Ltd.; any one or a combination of at least two of X9-470, NE-X-9500 of DIC Corporation.

[0044] Preferably, the thermosetting polyphenylene ether resin is a polyphenylene ether containing an unsaturated group, and more preferably a polyphenylene ether with an unsaturated group at the end.

[0045] Preferably, the unsaturated group includes any one or a combination of at least two of vinyl, styryl, propenyl, vinylbenzyl, vinylbenzyloxy, methacryloyloxy, allyl, acryloyloxy.

[0046] Preferably, the thermosetting polyphenylene ether resin has a structure shown in Formula III:

[0047]

[0048] Among them, k1 and k2 each independently selected from integers of 1-15, for example, can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15.

[0049] Y is selected from *-CH2-*, -* represents the connection site of the group.

[0050] X and Z each independently selected from any one of vinyl, styryl, propenyl, vinylbenzyl, vinylbenzyloxy, methacryloyloxy, allyl or acryloyloxy.

[0051] R 21 、R 22 、R 23 、R24 , R 25 , R 26 , R 27 , R 28 Each independently selected from hydrogen or methyl.

[0052] Preferably, the number-average molecular weight of the thermosetting polyphenylene ether resin is 1000 - 4000 g / mol. For example, it can be 1200 g / mol, 1500 g / mol, 1800 g / mol, 2000 g / mol, 2200 g / mol, 2500 g / mol, 2800 g / mol, 3000 g / mol, 3200 g / mol, 3500 g / mol or 3800 g / mol, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention does not exhaustively list all the specific point values included in the range.

[0053] As a preferred technical solution of the present invention, the number-average molecular weight of the thermosetting polyphenylene ether resin is 1000 - 4000 g / mol. It is compounded with a T-shaped polyvinyl siloxane resin and a maleimide compound, so that the resin composition has an appropriate curing rate, and the cured product contains a rich cross-linking network and a high cross-linking density, and has excellent dielectric properties, heat resistance, damp heat resistance and dielectric stability. If the number-average molecular weight of the thermosetting polyphenylene ether resin < 1000 g / mol, the reaction rate of the polyphenylene ether resin is too fast and difficult to control, and the dielectric properties of the formed resin composition become poor; if the number-average molecular weight of the thermosetting polyphenylene ether resin > 4000 g / mol, the melt viscosity of the polyphenylene ether resin is too high, and the compatibility with other resins becomes poor, and the prepared resin composition is prone to poor appearance.

[0054] In the present invention, the test method for the molecular weight (weight-average molecular weight, number-average molecular weight, etc.) is GB / T21863 - 2008, and it is measured by gel permeation chromatography (GPC) based on polystyrene calibration.

[0055] Preferably, the resin composition further includes a radical initiator.

[0056] Preferably, the radical initiator includes an organic peroxide.

[0057] Preferably, the radical initiator includes any one or a combination of at least two of di-tert-butyl peroxide, benzoyl peroxide, dilauroyl peroxide, cumyl peroxyneodecanoate, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, tert-butyl peroxyisobutyrate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxyacetate, tert-butyl peroxybenzoate, 1,1-di-tert-butyl peroxy-3,5,5-trimethylcyclohexane, 1,1-di-tert-butyl peroxycyclohexane, 2,2-bis(tert-butylperoxy)butane, bis(4-tert-butylcyclohexyl) peroxydicarbonate, hexadecyl peroxydicarbonate, tetradecyl peroxydicarbonate, di-tert-amyl peroxide, diisopropylbenzene peroxide, bis(tert-butylperoxyisopropyl)benzene, 2,5-dimethyl-2,5-di-tert-butylperoxyhexane, 2,3-dimethyl-2,3-diphenylbutane, 2,5-dimethyl-2,5-di-tert-butylperoxyhexyne, diisopropylbenzene hydroperoxide, cumene hydroperoxide, tert-amyl hydroperoxide, tert-butyl hydroperoxide, cumyl tert-butyl peroxide, diisopropylbenzene hydroperoxide, tert-butyl peroxy-2-ethylhexyl carbonate, tert-butyl peroxy-2-ethylhexyl carbonate, n-butyl 4,4-bis(tert-butylperoxy)valerate, methyl ethyl ketone peroxide, cyclohexanone peroxide.

[0058] Preferably, the mass parts of the radical initiator in the resin composition are 0.001 - 3 parts, for example, it can be 0.002 parts, 0.005 parts, 0.008 parts, 0.01 parts, 0.05 parts, 0.08 parts, 0.1 parts, 0.3 parts, 0.5 parts, 0.8 parts, 1 part, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts or 2.8 parts, as well as the specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention does not exhaustively list the specific point values included in the above range.

[0059] Preferably, the resin composition further includes a crosslinking agent.

[0060] Preferably, the crosslinking agent includes any one or a combination of at least two of divinylbenzene, divinyl benzyl ether, 1,2-bis(vinylphenyl)ethane, triallyl isocyanurate, triallyl cyanurate, cyanate ester, 1,2,4-trivinylcyclohexane, tricyclodecane dimethanol dimethacrylate, trimethylolpropane trimethacrylate, polyolefin resin containing a butadiene structure. Typical but non-limiting combinations include: for example, the combination of divinylbenzene and divinyl benzyl ether, the combination of 1,2-bis(vinylphenyl)ethane, triallyl isocyanurate and triallyl cyanurate, the combination of 1,2,4-trivinylcyclohexane, tricyclodecane dimethanol methacrylate, trimethylolpropane trimethacrylate and polyolefin resin containing a butadiene structure, etc.

[0061] Preferably, the mass parts of the crosslinking agent in the resin composition are ≤ 20 parts, and for example, it can be 0, 0.1 part, 0.2 part, 0.5 part, 1 part, 2 parts, 5 parts, 8 parts, 10 parts, 12 parts, 15 parts or 18 parts, as well as the specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention does not exhaustively list the specific point values included in the range.

[0062] Preferably, the resin composition further includes a phosphorus-based flame retardant.

[0063] Preferably, the phosphorus-based flame retardant includes phosphazene-based flame retardants and / or DOPO-based flame retardants.

[0064] Preferably, the phosphazene-based flame retardants include polyallylcyclotriphosphazene and / or polystyrylcyclophosphazene.

[0065] Preferably, the DOPO-based flame retardant is a flame retardant containing a 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide structure, and it can be any one or a combination of at least two of a compound with bis-DOPO linked by ethylene, a compound with bis-DOPO linked by propylene, a compound with bis-DOPO linked by phenylene, and a compound with bis-DOPO linked by biphenylene.

[0066] Preferably, the mass parts of the phosphorus-based flame retardant in the resin composition are 0.1 - 30 parts, and for example, it can be 0.2 part, 0.5 part, 1 part, 2 parts, 5 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts or 28 parts, as well as the specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention does not exhaustively list the specific point values included in the range.

[0067] Preferably, the resin composition further includes a filler, and the filler is an inorganic filler and / or an organic filler, and more preferably an inorganic filler.

[0068] Preferably, the inorganic filler includes any one or a combination of at least two of silica, aluminum nitride, boron nitride, silicon nitride, silicon carbide, aluminum oxide, magnesium oxide, titanium dioxide, barium titanate, strontium titanate, talc powder, magnesium carbonate, barium sulfate, calcium carbonate, and aluminum borate.

[0069] Preferably, the silica includes any one or a combination of at least two of crystalline silica, synthetic silica, spherical silica, fused silica, hollow silica, and chemically spherical silica.

[0070] Preferably, the average particle size (D 50) is 0.01 - 30 μm, for example, it can be 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm or 28 μm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention does not exhaustively list the specific point values included in the said range. Further preferably, it is 0.01 - 20 μm, and even more preferably, it is 0.01 - 10 μm.

[0071] Exemplarily, the particle size of the filler is measured by a MS3000 Malvern laser particle size analyzer.

[0072] Preferably, the mass parts of the filler in the resin composition are 10 - 200 parts, for example, it can be 20 parts, 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, 100 parts, 110 parts, 120 parts, 150 parts or 180 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention does not exhaustively list the specific point values included in the said range.

[0073] As a preferred technical solution of the present invention, the resin composition further includes an additive.

[0074] It should be noted that the present invention has no special restrictions on the specific dosage of the additive, and it can be added according to the type and requirements of the additive.

[0075] Preferably, the additive includes any one or a combination of at least two of a surfactant, an emulsifier, a toughening agent, a viscosity regulator, a pigment, and a curing accelerator. Typical but non - restrictive combinations include: a combination of an emulsifier and a surfactant, a combination of a toughening agent, a curing accelerator, and a pigment, a combination of a surfactant, an emulsifier, a toughening agent, a viscosity regulator, a pigment, and a curing accelerator, etc.

[0076] A solvent can also be added to the above resin composition. The addition amount of the solvent is selected by those skilled in the art according to experience and process requirements to make the resin composition reach a suitable viscosity for impregnation, coating, etc. of the resin composition. Subsequently, during the drying, semi - curing or full - curing process, the solvent in the resin composition will partially or completely volatilize.

[0077] The solvent of the present invention is not particularly limited, and exemplarily includes but is not limited to: ketones such as acetone, butanone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, aromatic hydrocarbons such as toluene, xylene, and mesitylene, esters such as ethoxyethyl acetate and ethyl acetate, nitrogen-containing solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone. The above solvents can be used alone or in combination of two or more, preferably aromatic hydrocarbon solvents such as toluene, xylene, and mesitylene are mixed with ketone solvents such as acetone, butanone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone.

[0078] In the process of dissolving or dispersing the resin composition in the solvent as described above, an emulsifier may be added, and dispersion by the emulsifier may allow the filler and the like to be evenly dispersed in the adhesive solution.

[0079] The resin composition provided by the present invention is prepared by the following method, which comprises: mixing and uniformly dispersing the components in the resin composition to obtain the resin composition.

[0080] In a second aspect, the present invention provides a resin film, wherein the material of the resin film includes the resin composition as described in the first aspect.

[0081] Preferably, the resin film is obtained by coating the resin composition on a release material and then drying and / or semi-curing the resin composition.

[0082] In a third aspect, the present invention provides a resin-coated copper foil, wherein the resin-coated copper foil comprises a copper foil layer and a resin layer, wherein the material of the resin layer comprises the resin composition as described in the first aspect.

[0083] Preferably, the resin-coated copper foil is obtained by coating the resin composition on a copper foil and then drying and / or semi-curing the resin composition.

[0084] In a fourth aspect, the present invention provides a prepreg, comprising a reinforcing material and the resin composition as described in the first aspect attached to the reinforcing material.

[0085] Preferably, the resin composition is attached to the reinforcing material by impregnation and then drying.

[0086] Preferably, the reinforcing material includes any one of natural fibers, organic synthetic fibers, organic fabrics, and inorganic fibers, or a combination of at least two thereof; such as glass fiber cloth, non-woven fabric, etc. Low dielectric reinforcing materials may also be selected as needed, such as NE glass fiber cloth, Q quartz cloth, QL cloth, etc.

[0087] Illustratively, the method for preparing the prepreg is: using the resin glue of the resin composition to impregnate a reinforcing material, and then drying to obtain the prepreg.

[0088] Preferably, the drying temperature is 100 - 180°C, for example, it can be 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C or 175°C, as well as the specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention does not exhaustively list the specific point values included in the range.

[0089] Preferably, the drying time is 1 - 30 min, for example, it can be 2 min, 5 min, 8 min, 10 min, 15 min, 20 min or 25 min, as well as the specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention does not exhaustively list the specific point values included in the range.

[0090] Fifthly, the present invention provides a copper clad laminate, which comprises at least one of the resin film as described in the second aspect, the resin-coated copper foil as described in the third aspect, and the prepreg as described in the fourth aspect.

[0091] Exemplarily, the copper clad laminate is prepared by the following method, which includes: laminating copper foil on one side or both sides of a semi-cured sheet and curing to obtain the copper clad laminate; or, laminating at least two semi-cured sheets into a laminate, laminating copper foil on one side or both sides of the laminate, and curing to obtain the copper clad laminate.

[0092] Preferably, the curing temperature is 150 - 250°C, for example, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C or 245°C, as well as the specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention does not exhaustively list the specific point values included in the range.

[0093] Preferably, the curing pressure is 10 - 60 kgf / cm 2 , for example, 15 kgf / cm 2 , 20 kgf / cm 2 , 25 kgf / cm 2 , 30 kgf / cm 2 , 35 kgf / cm 2 , 40 kgf / cm 2 , 45 kgf / cm 2 , 50 kgf / cm 2 or 55 kgf / cm 2 , as well as the specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention does not exhaustively list the specific point values included in the range.

[0094] Preferably, the curing time is 60 - 360 min, such as 80 min, 90 min, 100 min, 120 min, 140 min, 150 min, 160 min, 180 min, 200 min, 220 min, 240 min, 260 min, 280 min, 300 min, 320 min or 340 min, as well as the specific point values between the above point values. Due to space limitations and for the sake of brevity, the specific point values included in the scope of the present invention are not exhaustively listed herein.

[0095] In a sixth aspect, the present invention provides a printed circuit board, which includes at least one of the resin film as described in the second aspect, the resin-coated copper foil as described in the third aspect, the prepreg as described in the fourth aspect, and the copper-clad laminate as described in the fifth aspect.

[0096] Compared with the prior art, the present invention has the following beneficial effects:

[0097] (1) In the resin composition provided by the present invention, through the design of the T-shaped polyvinyl siloxane resin and its compounding and synergy with the maleimide compound and the thermosetting polyphenylene ether resin, the resin composition has a low dielectric constant Dk, a low dielectric loss tangent Df, a high glass transition temperature Tg, a low coefficient of thermal expansion CTE, and a low moisture absorption, achieving halogen-free flame retardancy, excellent heat resistance, heat and humidity resistance, and dielectric stability, effectively reducing the deterioration of dielectric properties in a humid environment, and having excellent comprehensive performance.

[0098] (2) Through the component design and optimization of the resin composition, the present invention enables the resin composition and the copper-clad laminate containing it to better balance dielectric properties, high heat resistance, and low moisture absorption, with Tg being 239 - 261 °C, Dk at 10 GHz being 3.78 - 3.91, Df ≤ 0.0055, Df after 96 h of double 85 treatment ≤ 0.0083, Df change rate ≤ 60%, Z-axis coefficient of thermal expansion CTE ≤ 1.4%, and having V-0 level flame retardancy, combining low dielectric loss, low moisture absorption, excellent dimensional stability, excellent dielectric properties, and dielectric stability. Specific Embodiments

[0099] The technical solutions of the present invention will be further described below through specific embodiments. Those skilled in the art should understand that the embodiments are only for helping to understand the present invention and should not be construed as specific limitations to the present invention.

[0100] In the following specific embodiments of the present invention, the materials involved are as follows:

[0101] (1) Maleimide compound

[0102] DFE950A, Sichuan Dongcai Science & Technology Co., Ltd.;

[0103] BMI2300, Daiwa Chemical Co., Ltd.;

[0104] BMI-70, KI Co., Ltd.

[0105] (2) Thermosetting polyphenylene ether resin

[0106] Methacryloyl-terminated polyphenylene ether resin, SA9000, Sabic Co., Ltd.;

[0107] Styrene-terminated polyphenylene ether resin, OPE-2st 2200, Mitsubishi Chemical Corporation.

[0108] (3) T-shaped multi-vinyl siloxane resin

[0109] Vinyl-terminated phenyl polyhedral oligomeric silsesquioxane resin, YK-253, with a vinyl content of 2 mmol / g, Zhejiang Winco New Materials Co., Ltd.;

[0110] Phenyl vinyl siloxane resin, PS-GV08, with a vinyl content of 3.0 mmol / g, Zhejiang Silicon Innovation Technology Co., Ltd.;

[0111] Phenyl vinyl siloxane resin, YK-252, with a vinyl content of 0.4 mmol / g, Zhejiang Winco New Materials Co., Ltd.

[0112] (4) Crosslinking agent

[0113] Triallyl isocyanurate, TAIC, Hunan Fangruida Technology Co., Ltd.

[0114] (5) Phosphorus-based flame retardant

[0115] DOPO-based flame retardant, a compound with bis-DOPO linked by ethylene, XP-7866, Albemarle Corporation.

[0116] (5) Free radical initiator

[0117] Organic peroxide, Perkadox BC-FF, AkzoNobel N.V.

[0118] (6) Filler

[0119] Fused silica, DQ1028L, Lianrui New Materials Co., Ltd.

[0120] (7) Reinforcing material

[0121] Fiberglass cloth, 2116E-fiberglass cloth, Shanghai Honghe Electronic Materials Co., Ltd.

[0122] (8) Copper foil

[0123] Electrolytic copper foil, Mitsui Mining & Smelting Co., Ltd.

[0124] Example 1

[0125] A resin composition comprising the following components by mass: 10 parts of maleimide compound BMI2300, 10 parts of maleimide compound BMI-70, 60 parts of thermosetting polyphenylene ether resin SA9000, 20 parts of T-type polyvinylsiloxane resin YK-253, 8 parts of phosphorus-based flame retardant XP-7866, 1 part of free radical initiator Perkadox BC-FF, and 100 parts of silica.

[0126] A prepreg and a copper clad laminate comprising the said resin composition, and the preparation method is as follows:

[0127] (1) Charge each component according to the formula amount, add 60 parts of toluene and 30 parts of methyl ethyl ketone, and mechanically stir for 4 h to dissolve and cure, and mix into glue.

[0128] (2) Pre-impregnate 2116E-glass fiber cloth in the glue obtained in step (1), remove part of the liquid resin through the nip rolls of rolling, control the resin on the glass fiber cloth at about 65%, and then dry the above glass fiber cloth in an oven at a temperature of 145 °C for 4.5 min to obtain a prepreg.

[0129] (3) Prepare 2 electrolytic copper foils with a thickness of 18 μm, laminate 5 prepregs obtained in step (2), and align the four sides neatly. After covering 1 prepared electrolytic copper foil on each of the upper and lower surfaces of the laminate, put it into a laminator and laminate according to the following conditions: Heat up the laminator, apply full pressure when reaching 90 °C, and the full pressure is 30 kgf / cm 2 ; Continue to heat up. When reaching 120 °C, control the heating rate of the material temperature at 2 °C / min until 220 °C, and hold for 120 min for curing to obtain a copper clad laminate.

[0130] Examples 2-6, Comparative Examples 1-5

[0131] A resin composition, and its specific formula is shown in Table 1; the dosage unit of each component in Table 1 is "part".

[0132] Prepare the resin compositions of Examples 2-6 and Comparative Examples 1-5 into prepregs and copper clad laminates by the method described in Example 1, and conduct the following physical property evaluation tests:

[0133] (1) Glass transition temperature Tg (°C): Measured by dynamic thermomechanical analysis (DMA) according to the DMA method specified in IPC-TM-650 2.4.24.4.

[0134] (2) Dielectric constant Dk and dissipation factor Df: Measured at 10 GHz using the Split Post Dielectric Resonator (SPDR) method as specified in IPC-TM-650 2.5.5.13;

[0135] (3) Df after high temperature and high humidity treatment: Treated at 85°C and 85% humidity (double 85 treatment) for 96 h, and then measured at 10 GHz using the Split Post Dielectric Resonator (SPDR) method;

[0136] Df change rate = (Df after double 85 treatment - initial Df) / initial Df;

[0137] (4) Flame retardancy: Tested and classified according to the material flammability method specified in UL-94;

[0138] (5) Coefficient of thermal expansion CTE: Tested for the thermal expansion rate of the board in the Z-axis direction from 50 to 260°C according to the method specified in IPC-TM-650 2.4.24;

[0139] The test results are shown in Table 1.

[0140] Table 1

[0141]

[0142]

[0143] According to the data in Table 1, it can be seen that in the resin composition provided by the present invention, through the design of the T-shaped polyvinyl siloxane resin and its compounding and mutual synergy with the maleimide compound and the thermosetting polyphenylene ether resin, the resin composition achieves halogen-free flame retardancy, excellent dielectric properties, heat resistance, moisture resistance, and dielectric stability, effectively avoiding the deterioration of dielectric properties in a humid environment. The copper clad laminate containing it has a V-0 grade flame retardancy, a Tg of 239-261°C, a Dk of 3.78-3.91 at 10 GHz, a Df of 0.005-0.0055, a Df of 0.008-0.0083 after double 85 treatment for 96 h, a Df change rate of 49-60%, and a Z-axis coefficient of thermal expansion CTE of 1.15-1.4%, with excellent comprehensive performance.

[0144] Comparing Examples 1-4 with Comparative Examples 1-3, it can be seen that if the resin composition does not contain the T-shaped polyvinyl siloxane resin, it has high hygroscopicity, a significant increase in Df in a humid and hot environment, and obvious deterioration of dielectric properties.

[0145] Comparing Example 1 with Comparative Example 4, it can be seen that if the content of vinyl groups in the T-shaped polyvinyl siloxane resin in the resin composition is too low, the heat resistance is poor and the CTE is poor.

[0146] Comparing Example 1 with Comparative Example 5, it can be seen that if the content of the T-type polyvinyl siloxane resin in the resin composition is too high, the heat resistance is poor and the change rate of Df is large in a humid and hot environment.

[0147] The applicant declares that the resin composition, the copper clad laminate and the printed circuit board containing the same of the present invention are illustrated by the above embodiments, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, the equivalent replacement of each raw material of the product of the present invention, the addition of auxiliary components, the selection of specific methods, etc. all fall within the protection scope and the disclosure scope of the present invention.

Claims

1. A resin composition, characterized in that, The resin composition comprises the following components in parts by mass: 10 - 20 parts of T - type polyvinyl siloxane resin 10 - 30 parts of maleimide compound 30 - 80 parts of thermosetting polyphenylene ether resin; In the T - type polyvinyl siloxane resin, the content of vinyl groups ≥ 1.5 mmol / g.

2. The resin composition according to claim 1, wherein The T-type polyvinyl siloxane resin contains at least one RSiO 3 / 2 group and at least one CH2=CH(CH3)2SiO 1 / 2 group; wherein, R is a phenyl group; Preferably, the T-shaped polyvinyl siloxane resin contains (RSiO 3 / 2 ) a (CH2=CH(CH3)2SiO 1 / 2 ) b ((CH3)3SiO 1 / 2 ) c structure; wherein a, b, and c are each independently selected from integers of 1-30, and the R is a phenyl group; Preferably, the T - type polyvinyl siloxane resin includes vinyl - containing polyhedral oligomeric silsesquioxane resin; Preferably, the T - type polyvinyl siloxane resin has the structure shown in Formula I: wherein, R1 and R2 are each independently selected from any one of; -* represents the connection site of the group; m, n, p each independently selected from integers of 1 - 15.

3. The resin composition according to claim 1 or 2, characterized in that, The maleimide compound is a maleimide resin containing at least two imine ring structures in the molecular structure; Preferably, the maleimide compound has the structure shown in Formula II: Wherein, n1 is selected from integers of 1 - 10; L is selected from *-CH2-*, -* represents the connection site of the group; R 11 、R 12 、R 13 Each independently selected from any one of C1-C5 straight-chain or branched-chain alkyl groups and phenyl groups; m1, m2, m3 each independently selected from integers of 0 - 3; s is selected from integers of 1 - 5.

4. The resin composition according to any one of claims 1 to 3, characterized in that, The thermosetting polyphenylene ether resin is a polyphenylene ether containing unsaturated groups, preferably a polyphenylene ether with unsaturated groups at the end groups; Preferably, the thermosetting polyphenylene ether resin has the structure shown in Formula III: Wherein, k1, k2 each independently selected from integers of 1 - 15; Y is selected from *-CH2-*, -* represents the connection site of the group; X, Z each independently selected from any one of vinyl, styryl, allyl, vinylbenzyl, vinylbenzyloxy, methacryloyloxy, allyl or acryloyloxy; R 21 、R 22 、R 23 、R 24 、R 25 、R 26 、R 27 、R 28 each independently selected from hydrogen or methyl; Preferably, the number - average molecular weight of the thermosetting polyphenylene ether resin is 1000 - 4000 g / mol.

5. The resin composition according to any one of claims 1 to 4, characterized in that, The resin composition further comprises a radical initiator; Preferably, the radical initiator includes organic peroxides, further preferably any one or a combination of at least two of di - tert - butyl peroxide, benzoyl peroxide, dilauroyl peroxide, cumyl peroxyneodecanoate, tert - butyl peroxyneodecanoate, tert - butyl peroxypivalate, tert - butyl peroxyisobutyrate, tert - butyl peroxy - 3,5,5 - trimethylhexanoate, tert - butyl peroxyacetate, tert - butyl peroxybenzoate, 1,1 - di - tert - butyl peroxide - 3,5,5 - trimethylcyclohexane, 1,1 - di - tert - butyl peroxide cyclohexane, 2,2 - bis(tert - butylperoxy)butane, bis(4 - tert - butylcyclohexyl) peroxydicarbonate, peroxydicarbonate hexadecyl ester, peroxydicarbonate tetradecyl ester, di - tert - amyl peroxide, diisopropylbenzene peroxide, bis(tert - butylperoxyisopropyl)benzene, 2,5 - dimethyl - 2,5 - di - tert - butylperoxyhexane, 2,3 - dimethyl - 2,3 - diphenylbutane, 2,5 - dimethyl - 2,5 - di - tert - butylperoxyhexyne, diisopropylbenzene hydroperoxide, cumene hydroperoxide, tert - amyl hydroperoxide, tert - butyl hydroperoxide, cumene hydroperoxide, tert - butyl peroxy - 2 - ethylhexyl carbonate, tert - butyl peroxy - 2 - ethylhexyl carbonate, 4,4 - bis(tert - butylperoxy)valeric acid n - butyl ester, methyl ethyl ketone peroxide, cyclohexanone peroxide; Preferably, the mass parts of the radical initiator in the resin composition is 0.001 - 3 parts; Preferably, a crosslinking agent is further included in the resin composition; Preferably, the crosslinking agent includes any one or a combination of at least two of divinylbenzene, divinyl benzyl ether, 1,2-bis(vinylphenyl)ethane, triallyl isocyanurate, triallyl cyanurate, cyanate ester, 1,2,4-trivinyl cyclohexane, tricyclodecane dimethanol dimethacrylate, trimethylolpropane trimethacrylate, and polyolefin resin containing a butadiene structure; Preferably, the mass part of the crosslinking agent in the resin composition is 0.1-20 parts; Preferably, a phosphorus-based flame retardant is further included in the resin composition; Preferably, the phosphorus-based flame retardant includes a phosphazene-based flame retardant and / or a DOPO-based flame retardant; Preferably, the mass part of the phosphorus-based flame retardant in the resin composition is 0.1-30 parts; Preferably, a filler is further included in the resin composition; Preferably, the mass part of the filler in the resin composition is 10-200 parts.

6. A resin film, characterized in that, The material of the resin film includes the resin composition according to any one of claims 1-5.

7. A resin-coated copper foil, characterized in that, The resin-coated copper foil includes a copper foil layer and a resin layer, and the material of the resin layer includes the resin composition according to any one of claims 1-5.

8. A prepreg, characterized in that, The prepreg includes a reinforcing material and the resin composition according to any one of claims 1-5 attached to the reinforcing material.

9. A copper clad laminate, characterized in that, The copper clad laminate includes at least one of the resin film according to claim 6, the resin-coated copper foil according to claim 7, and the prepreg according to claim 8.

10. A printed circuit board, characterized in that, The printed circuit board includes at least one of the resin film according to claim 6, the resin-coated copper foil according to claim 7, the prepreg according to claim 8, and the copper clad laminate according to claim 9.

Citation Information

Patent Citations

  • Preparation method of polyphenyl ether adhesive and copper-clad plate thereof

    CN104263306A

  • Resin composition

    CN105936745A